Revitalizing The Professionalism of Early Childhood Education Teachers As A Key to Improving The Quality of Early Childhood Education Services - Laila Robiatul Adawiah; Sahrona Harahap; Devita Savitri; Mildayani Suhana; Siti Nurmaidah Varuq (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
Revitalizing the professionalism of Early Childhood Education (ECE) teachers is an urgent need in order to enhance the quality of early childhood education services, particularly in rural areas such as Singajaya District, Garut Regency. ECE teachers are required not only to possess strong pedagogical competence, but also to adapt to the dynamics of the times and to understand the local characteristics of their students. This study aims to analyze strategies for revitalizing teacher professionalism as a key to improving the quality of educational services. A descriptive qualitative approach with a case study method was employed. The research subjects consisted of ECE teachers in Singajaya District. Data were collected through observation, open-ended questionnaires, focus group interviews, and document analysis. Data analysis was conducted using the Miles and Huberman interactive model, which includes three stages: data reduction, data display, and conclusion drawing. The findings indicate that enhancing teacher professionalism can be achieved through locally-based training, the establishment of teacher learning communities, educative supervision, and regulatory support from local governments. Moreover, integrating local cultural values into the learning process is a critical strategy in developing reflective and adaptive educators. The study concludes that revitalizing teacher professionalism not only improves individual competencies but also strengthens a more responsive and higher-quality ECE service ecosystem.